2012
DOI: 10.1371/journal.pone.0043470
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Circulating Plasma hTERT mRNA Is a Useful Marker for Prostate Cancer Diagnosis and Is Associated with Poor Prognosis Tumor Characteristics

Abstract: BackgroundSerum prostate-specific antigen (PSA) is the most widely used marker for diagnosing prostate cancer (PCa). It lacks specificity and predictive value, resulting in inaccurate diagnoses and overtreatment of the disease. The aim of this study was to assess the usefulness of plasma telomerase reverse transcriptase (hTERT) mRNA as a diagnostic and prognostic tool for PCa and its association with clinicopathological parameters of tumors.Principal FindingsPlasma hTERT mRNA levels were determined by qRT-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 26 publications
1
53
0
Order By: Relevance
“…There are numerous reports describing the connection of extracellular mRNA in connection with cancer diagnostics. For instance, Koperski et al described detection of tumor‐related tyrosinase mRNA in melanoma patients , Fleischhacker et al referred similar findings with hnRNP‐B1 and HER2/neu‐specific mRNA from sera of patients with malignant lung tumor , and results of study of March‐Villalba et al indicate that hTERT mRNA is an effective molecular marker for the diagnosis of prostate cancer . Based on our results, although serum MT2A mRNA appears to be a prospective marker for the diagnosis of prostate cancer, further studies including higher number of patients are required to validate its diagnostic value.…”
Section: Discussionsupporting
confidence: 80%
“…There are numerous reports describing the connection of extracellular mRNA in connection with cancer diagnostics. For instance, Koperski et al described detection of tumor‐related tyrosinase mRNA in melanoma patients , Fleischhacker et al referred similar findings with hnRNP‐B1 and HER2/neu‐specific mRNA from sera of patients with malignant lung tumor , and results of study of March‐Villalba et al indicate that hTERT mRNA is an effective molecular marker for the diagnosis of prostate cancer . Based on our results, although serum MT2A mRNA appears to be a prospective marker for the diagnosis of prostate cancer, further studies including higher number of patients are required to validate its diagnostic value.…”
Section: Discussionsupporting
confidence: 80%
“…Still, specific RNAs can be released from cancer cells into biofluids, allowing their identification and further determination of their potential value as biomarkers, as they may mirror the cellular state within the concept of liquid biopsy. For instance, some RNA transcripts were already evidenced and found increased in plasma, as is the case of telomerase reverse transcriptase (hTERT) that showed diagnostic and prognostic value for prostate cancer, being a good predictor of recurrence [35,36]. Similarly, the levels of the long non-coding RNA prostate cancer associated 3 (PCA3) were abundantly found in urine of patients with prostate cancer, constituting a promising non-invasive biomarker for the diagnosis of that cancer [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, the expression pro le of hTERT showed close link with clinical factors and disease-free survival of the patients that might be a potential prognostic biomarker for the cancer [30]. The plasma hTERT mRNA level was signi cantly different between healthy individuals and prostate cancer cases, and ROC analysis demonstrated that hTERT was an useful non-invasive diagnostic biomarker for the disease [31]. Taken together, hTERT might be a potential molecular biomarker for human cancer that might be widely used for early detection, targeted treatment, and prognosis evaluation in tumor.…”
Section: Discussionmentioning
confidence: 99%